Defining gastrointestinal transit time using video capsule endoscopy: a study of healthy subjects - O’Grady, John; Murphy, Clodagh L.; Barry, Lillian; Shanahan, Fergus; Buckley, Martin (Endoscopy International Open, 2020)
Background and study aims Determining the etiology and location of gastrointestinal motility disorders can be challenging. A range of investigations targeting specific areas of gastrointestinal transit are available, but many provide clinical data for a given gastrointestinal region alone or for non-specific whole gut transit, and are otherwise of limited use. Video capsule endoscopy allows endoscopic visualisation of the entire gastrointestinal tract, and may also provide more specific data for regional transit time abnormalities.Patients and methods Data from video capsules ingested by 71 ambulatory healthy subjects were recorded and analyzed to determine gastric and small bowel transit times in the fasting state.Results Median, and interquartile range (IQR), gastric transit time was 22 (10–48) minutes, and median (IQR) small bowel transit time was 198.5 (157–240.5) minutes.Conclusion These data, for the first time to our knowledge, provide references for gastrointestinal transit times among healthy ambulatory subjects using video capsule endoscopy. This potentially strengthens clinical use of video capsule endoscopy in the investigation of patients with suspected gastrointestinal motility disorders.